2022
DOI: 10.1039/d2dt01124g
|View full text |Cite
|
Sign up to set email alerts
|

The impact of secondary coordination sphere engineering on water oxidation reactivity catalysed by molecular ruthenium complexes: a next-generation approach to develop advanced catalysts

Abstract: Water oxidation is the bottleneck to producing hydrogen from the water-splitting reaction. The development of efficient water oxidation catalysts (WOCs) is of paramount interest in recent years. Ru-based WOCs have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…A first‐order behaviour with respect to the catalyst indicates a mononuclear mechanism, likely operating via WNA for O−O bond formation. It may be speculated that the non‐coordinating N‐atom of the in ‐positioned imidazo[4,5‐ b ]pyridine moiety in 2 may H‐bond to incoming water and thus assist a WNA mechanism at a high‐valent Ru=O intermediate [52,53] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A first‐order behaviour with respect to the catalyst indicates a mononuclear mechanism, likely operating via WNA for O−O bond formation. It may be speculated that the non‐coordinating N‐atom of the in ‐positioned imidazo[4,5‐ b ]pyridine moiety in 2 may H‐bond to incoming water and thus assist a WNA mechanism at a high‐valent Ru=O intermediate [52,53] …”
Section: Resultsmentioning
confidence: 99%
“…It may be speculated that the non-coordinating N-atom of the in-positioned imidazo [4,5-b]pyridine moiety in 2 may H-bond to incoming water and thus assist a WNA mechanism at a high-valent Ru=O intermediate. [52,53] To gain information about the complex species present in solution after catalysis, solutions of 2 in a 1 : 1 mixture of 0.10 M triflic acid (pH 1.0) and TFE (viz., conditions as above) were treated with 30 equiv. CAN, and ESI(+) mass spectra were then recorded.…”
Section: Water Oxidation Catalysis With Ce IV As a Chemical Oxidantmentioning
confidence: 99%
“…The development of an effective secondary coordination environment has recently been introduced to Ru-based WOCs. [37][38][39]53,67 Several strategies have been used, as shown in Fig. 1.…”
Section: Catalysis Science and Technology Perspectivementioning
confidence: 99%
“…37 Although ligands in the primary coordination sphere directly influence the steric and electronic properties of the metal center, the secondary coordination sphere also needs to be assessed during catalyst engineering. 36,38,39 For instance, literature studies have demonstrated that smallmolecule catalysis, such as the reduction of CO 2 , O 2 , H + , and oxidation of NH 3 and H 2 O, could benefit rationally by finetuning the secondary coordination sphere of the corresponding catalysts. [40][41][42][43][44][45][46] The manipulation of the secondary coordination sphere of Ru-based WOCs has primarily been achieved via non-covalent interactions, such as hydrogen bonding, π-π stacking, hydrophobic/hydrophilic effects, steric hindrance, and electronic influence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation